Bioinspired Manganese Complexes and Graphene Oxide Synergistically Catalyzed Asymmetric Epoxidation of Olefins with Aqueous Hydrogen Peroxide. Issue 3 (23rd January 2017) - Miao, Chengxia; Yan, Xingbin; Xu, Daqian; Xia, Chungu; Sun, Wei
Abstract: Bioinspired manganese complexes of N4 ligands and graphene oxide (GO) synergistically catalyze the highly enantioselective epoxidation of olefins (up to 99% ee ), which is a rare example with GO as a co‐catalyst in asymmetric catalysis. GO as a new and key additive not only successfully functions in catalytic amounts, but also has a positive effect for improving the enantioselectivity of the asymmetric epoxidation compared with the traditional stoichiometric organic carboxylic acid method [e.g., chalcone, 95% ee (3.5 mg GO) vs . 84% ee (5 equiv., 75 mg acetic acid), ethyl cinnamate, 84% ee (3.5 mg GO) vs . 19% ee (5 equiv., 75 mg acetic acid)]. The X‐ray photoelectron spectroscopy (XPS) spectra of GO before and after the reaction indicate that the intensities of C–O become stronger after the reaction, which may have a certain relationship with hydrogen peroxide (H2 O2 ) and gives a reasonable rationale for the large consumption of H2 O2 . Also, part of the hydrogen peroxide was used for the oxidation of GO. Abstract :